2021 Social Accounting Matrix (SAM) for Kenya: An instrument for policy analysis and simulation - Omune, Lensa; Mbuthia, Juneweenex (CGIAR System Organization, 2023)
The updated Kenya SAM incorporates latest rebased national accounts data, supply and use tables and household budget survey, is an update of the previous SAM compiled for 2009 transactions. SAMs are used in conjunction with analytical techniques to strengthen the evidence underlying policies to promote sustainable economic growth and reduce poverty and inequality. The updated Kenya SAM 2021 identifies 90 production activities and commodities (products) across agriculture, industry, and services sectors. The SAM also includes 3 broad categories of production factors (land, capital and labor), and 15 household groups by quintiles.